An Analysis of Internet Abuses Impact on Children's Moral Development - Zadrian Ardi; Kharina Viola; Indah Sukmawati (Indonesian Institute for Counseling, Education and Therapy (IICET), 2018)
The Internet is an open, global communications network that connects over thousands of computer networks, over an individual public or private telephone line, its component network is managed by agents from governments, universities, commercial organizations, and volunteers. Teenagers are the largest individual internet users, which the internet has a positive or negative impact or influence. Positive impact we can get information easily. However, the internet can affect the moral development of adolescents, because of the negative impact of the internet itself. Teenagers misuse of the internet, for example teenagers often watch porn on the internet, which will result in an influence on adolescent morale. With regard to the position of the counselor, then the dimensions of internet use that tend to be more widely used by teenagers, internet counseling will be more efficient and effective.